A staged approach to managing a combination of a terrible triad injury and an Essex–Lopresti fracture dislocation: an open forearm crush injury—a case report - Abdulla Abdelwahab; Ahmed Khairy Farahat Elsayed; Hamed Badawi (Journal of Medical Case Reports, 2024)
Abstract Background Open and crushed forearm injury is a complex and rare injury affecting the upper extremity. It results in damage to various structures, including bones, soft tissues, and neurovascular bundles, ultimately leading to functional impairment. Typically, these injuries occur owing to high-energy trauma. Case presentation A 19-year-old South Asian male was seen at our trauma center emergency department following an accident where his arm got entangled in a machine belt. He sustained a serious open injury on his left forearm, spanning from the elbow to the wrist, affecting the proximal radio-ulnar joint, ulna bone, interosseous membrane, and distal radio-ulnar joint. The initial plan of care involved stabilizing the injury using an external fixator, while reconstructive surgery was scheduled for a later date. Conclusion Timely intervention for wound debridement and joint stabilization plays a crucial role in the restoration of a crushed forearm. Following this, a collaborative effort from a multidisciplinary team becomes essential. Planning multiple surgeries is important, with the primary goal of achieving early range of motion of the elbow and wrist to prevent stiffness. This comprehensive approach aims at optimizing the recovery and functionality of the affected limb. The combination of early intervention, damage control surgeries, and carefully planned procedures sets the foundation for successful management of a crushed and open forearm injury. Furthermore, early range of motion and physiotherapy rehabilitation has a key role in stiffness prevention and the restoration of function.